Obstetrics injuries during shoulder dystocia in a tertiary perinatal center. (November 2022) - Habek, Dubravko; Prka, Matija; Luetić, Ana Tikvica; Marton, Ingrid; Medić, Filip; Miletić, Antonio Ivan
Highlights: Fetal shoulder dystocia or incarceration of fetal shoulders is peracute and mostly unpredictable obstetric complication. Our results confirmed that strategy of prompt identification of SD accompanied by cessation of axial fetal head traction decrease the risk of brachial plexus strain. We think that our good results corelates with our opinion that the performance of external obstetrical maneuvers should be done without one minute postpone since efforts should be put in sooner shoulder liberation decreasing the time of fetal hypoxia. Proper medical documentation should not be neglected. We can conclude that our results confirm our experience and our approach to the fetal SD philosophy with the goal of obstetrical injuries and permanent disability reduction as a globally major problem of SD. Abstract: Objectives: This study will present our results in management of fetal shoulder dystocia with special consideration of maternal and neonatal outcome. Study design. A retrospective study was performed at a university tertiary perinatal center. The study included data of singleton vaginal term deliveries in the period of 15 years (2006–2020). Analized informations include: obstetrics maternal and neonatal data and outcomes. Results: This period included 45, 687 deliveries with diagnosed shoulder dystocia in 254 (0.7 %) cases in vaginal deliveries. Most of the deliveries were spontaneous births 69.7 %, induced deliveries 30.3 %, 47.2 % primiparas and preexisting or gestational diabetes in 21.7 %. The delivery was managed by vacuum extraction in 13.8 %, mediolateral episiotomy in 48.0 % of births, most of the shoulder dystocia were unilateral anterior, while only two cases were diagnosed as more difficult bilateral and 5 cases were recurrent. 87.4 % cases were resolved by McRobert's maneuver, 7.8 % by Barnum's 3.9 % by Wood's maneuver and one case was managed by Menticoglou and by Bourgoise-Siegemundin maneuver. 4.3 % injuries were classified as OASIS of III/IV degree, early postpartum hemorrhage due in 1.6 %. 54.3 % of newborns were male sex, 61.0 % of newborns had birth weight of above 4000 g (mean 4071 g). Maximal Apgar scores were atributed to 92.5 % in first and to 97.2 % in fifth minute, one case that requaired resuscitation. Clavicle fracture was found in 9.5 %, humerus fracture in 0.4 %, transient form of Duchenne Erb obstetrics brachial palsy was diagnosed in only in 7.5 % newborns, while we have not found any case of permanent brachial palsy. Conclusions: Our results confirmed that strategy of prompt identification of shoulder dystocia accompanied by cessation of axial fetal head traction decrease the risk of brachial plexus strain, injury or tear, while performance of exact obstetrical maneuvers resulted in decanceration of fetal shoulders without permanent obstetrics brachial palsy or cerebral morbidity. We think that our good results corelate with our opinion that the performance of external obstetrical manoeuvres should be done without one minute postpone since efforts should be put in sooner shoulder liberation decreasing the time of fetal hypoxia.